(untitled) (Web of Teachers: Inderscience Research, 2024)
The role of dual education, features, advantages and disadvantages of dual education in the training of qualified engineer-technical personnel in the field of alternative energy are considered. The dual education system is a flexible and effective mechanism that enables the training of highly qualified specialists required in the activities of modern production enterprises.